The Influence of Government Subsidy and Pro-environmental Gaps on Electricity-saving Behaviors of Households in Indonesia - Dimas Abi Aufan (Pusbindiklatren Bappenas, 2020)
This research analyzes whether electricity subsidy as an external factor and pro-environmental intention and acts as internal factors have any relationship on households' electricity-saving behaviors in Indonesia. To this end, Indonesia's household data from the National Socioeconomic Survey of Indonesia (SUSENAS) in 2017 is empirically analyzed. Using logit regression with control factors such as dwellings and sociodemographic characteristics, the statistical analysis reveals that subsidized households areless likely to save electricity in their daily lives. Furthermore, families with higher pro-environmental intentions are not necessarily likely to save electricity, while households who are accustomed to pro-environmental routines are likely to do so. These demonstrate the existence ofinternal gaps between their pro-environmental intention and the acts, suggesting that electricity subsidies reform and program should be considered along with the way how intention-act gaps can be mitigated at household levels for energy saving.